Electrodeposition of Copper-Silver Alloys from Aqueous Solutions: A Prospective Process for Miscellaneous Usages - Sofya Efimova; Florica Simescu Lazar; Jean-Paul Chopart; François Debray; Anne-Lise Daltin (Compounds)
The electrodeposition of copper (Cu), silver (Ag), and their alloys has been a subject of interest since the 19th century. Primarily due to their exceptional features such as good mechanical hardness and electrical conductivity, high resistance to corrosion, and electromigration, Cu–Ag electrodeposits continue to be investigated and developed to improve their properties for different applications. This paper reviews the state of the art in the field of electroplated Cu–Ag alloys in an aqueous solution, with particular emphasis on the observed properties and variety of electrochemical processes used to produce high-quality materials. Moreover, this review paper focuses on the experimental conditions employed for Cu–Ag electrodeposition, intending to understand the basis and manipulate the processes to obtain coatings with superior characteristics and for attractive usage. Finally, the most trending applications of these coatings are discussed depending on different parameters of electrodeposition to provide prospects for potential research.